Second Language Teachers' Knowledge and Beliefs About Dyslexia: Turkish Context - Yuksel, H. Gulru; Ozcan, Emrah (WILEY, 2025)
Dyslexia is one of the most common language-based learning disabilities. Teaching a second language (L2) to dyslexic students is still a contested issue among educators. Teachers' knowledge and beliefs about dyslexia play an important role in the successful inclusion of these students in L2 classrooms. The current study investigated the knowledge and beliefs of Turkish second language teachers (SLTs) about dyslexia. Data were collected from 150 participants using the Knowledge and Beliefs About Developmental Dyslexia Scale (KBDDS). The findings revealed that Turkish SLTs possess a moderate level of knowledge about dyslexia, with notable strengths in understanding the need for individualised instruction and rejecting common myths, such as the belief that dyslexia is linked to laziness or low intelligence. However, several misconceptions persist, including the belief that dyslexia primarily results from visual processing issues. Female teachers and those with less than 11 years of teaching experience demonstrated significantly higher levels of knowledge. The study highlights the need for targeted professional development that builds on teachers' existing strengths while addressing areas of misunderstanding. Further research is recommended to explore the impact of teacher knowledge on dyslexic students' learning outcomes in L2 classrooms.
Keywords: dyslexia; misconceptions; second language teacher; teacher knowledge; UNDERSTANDING DYSLEXIA; LANGUAGE; ENGLISH; CHILDREN; SKILLS; DIFFICULTIES; PERCEPTIONS; PRESERVICE; PREVALENCE; MOTIVATION; Education & Educational Research; Psychology; Rehabilitation